2013
DOI: 10.4028/www.scientific.net/amm.444-445.1379
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis and Simulation of the Sealing Performance of Y-Ring Rubber Seal

Abstract: Application of super elasticity theory and nonlinear theory, based on finite element method and the Abaqus software, the performance of Y ring rubber seal, such as the Von Mises stress, the sealing ring deformation and the contact pressure were simulated and analyzed under the influence of changeable hydraulic pressure. According to seal failure criterion, the effect of hydraulic pressure changes on the sealing performance were studied. Results show that, the maximum stress appears in the intersection of lips,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…In order to study the deformation-stress of the rubber ring caused by boundary condition of assemble status, three kind of installation modes are assigned according to the Reference [30]. As schematic Figure 4 shown, piston rod axial displacement (RA), piston rod lateral displacement (RL), and groove lateral displacement (GL) are taken into account [15]. The conventional installation modes are presented in Figure 4b,c, e.g., piston rod is set with a rigid displacement in lateral direction and groove is set with a fixed constraint considered installation mode of RL.…”
Section: Installation Modementioning
confidence: 99%
See 1 more Smart Citation
“…In order to study the deformation-stress of the rubber ring caused by boundary condition of assemble status, three kind of installation modes are assigned according to the Reference [30]. As schematic Figure 4 shown, piston rod axial displacement (RA), piston rod lateral displacement (RL), and groove lateral displacement (GL) are taken into account [15]. The conventional installation modes are presented in Figure 4b,c, e.g., piston rod is set with a rigid displacement in lateral direction and groove is set with a fixed constraint considered installation mode of RL.…”
Section: Installation Modementioning
confidence: 99%
“…The sealing characteristic of Y-ring relied on the surface of lips to coupling, as a lip-type rubber ring. Cui analyzed the effect of hydraulic pressure on Y-ring sealing performance, and found out the location of the maximum stress and largest deformation area according to seal failure criterion [15]. The disadvantage of thresh tendency under high pressure is a weakness for Y-ring.…”
Section: Introductionmentioning
confidence: 99%
“…O-ring seals used in oil and gas pipelines are exposed to extreme environments such as large changes in temperature, pressure, and conveyed fluid [5]. Furthermore, depending on the geometry of O-ring seals, they are exposed to highly complex operating conditions as they are compressed and constrained.…”
Section: Introductionmentioning
confidence: 99%
“…Cui et al [5] applied nonlinear theory to investigate the performance of Y-ring seals under the influence of hydraulic pressure. Based on the failure criterion (i.e., von Mises stress), the location showing the maximum contact stress and the largest deformation was suggested, which could cause aggravated wear.…”
mentioning
confidence: 99%
“…To reduce the contact pressure and contact area, Zhou and Liu 5 and Zeng et al 6 designed a bionic non-smooth surface seal with conical teeth. Cui et al 7 analyzed the failure of a kind of Y-ring rubber seal and found that greater contact pressure would result in bitten phenomenon or aggravate wear. Zheng et al 8 used computer-aided simulation technology to optimize a kind of π -shape seal.…”
Section: Introductionmentioning
confidence: 99%